ANALISIS MINAT MAHASISWA MENDENGARKAN APLIKASI MUSIK BERBAYAR DAN UNDUHAN MUSIK GRATIS - Johanes Fernandes Andry; Calvin Tjee (Universitas Bunda Mulia, 2019)
Nowadays, music has already become one of people’s life styles. People could download music from websites. However they don’t know whether the music that they have downloaded is authentic from the producer or not. People should listen to authentic music. And the appearance of Spotify, music streaming application, allow people to listen to music with guaranteed sound quality because Spotify has the copyright for musics that they have uploaded. To enjoy the Spotify’s services, users are obligated to pay the monthly service fee. On the other hand, Spotify offers one month free service to new users that have registered on Spotify’s Website. Based on these explanations,the purpose of this research is to know about how big does the interest of XYZ University’s Student from all majors in paid music streaming application especially Spotify and free downloaded music via website. The methods that is being use in this research is quantitative method with purposive sampling technique which is to distribute questionnaire to the students. After distributed the questioners, researcher is going to analyze the data with validity test, reliability test and hypothesis test by using SPSS software. The research result shows that people is interested in using paid music application.